A genome-wide analysis in consanguineous families reveals new chromosomal loci in specific language impairment (SLI) - Andres, Erin M.; Hafeez, Huma; Yousaf, Adnan; Riazuddin, Sheikh; Rice, Mabel L.; Basra, Muhammad Asim Raza; Raza, Muhammad Hashim (European journal of human genetics : EJHG, 2019)
Language is a uniquely human ability, and failure to attain this ability can have a life-long impact on the affected individuals. This is particularly true for individuals with specific language impairment (SLI), which is defined as an impairment in normal language development in the absence of any other developmental disability. Although SLI displays high heritability, family-based linkage studies have been hampered by an unclear mode of Mendelian segregation, variable disease penetrance, and heterogeneity of diagnostic criteria. We performed genome-wide parametric linkage analysis and homozygosity mapping in 14 consanguineous families from Pakistan segregating SLI. Linkage analysis revealed a multipoint LOD score of 4.18 at chromosome 2q in family PKSLI05 under a recessive mode of inheritance. A second linkage score of 3.85 was observed in family PKSLI12 at a non-overlapping locus on chromosome 2q. Two other suggestive linkage loci were found in family PKSLI05 on 14q and 22q with LOD scores of 2.37 and 2.23, respectively, that were also identified in homozygosity mapping. Reduction to homozygosity was observed on chromosomes 2q, 5p, 8q, 14q, 17q, and 22q. Each homozygosity region occurred in multiple PKSLI families. We report new SLI loci on chromosomes 2 and 8 and confirm suggestive SLI linkage loci on chromosomes 5, 14, 17, and 22 reported previously in the population of Robinson Crusoe Island. These findings indicate that linkage and homozygosity mapping in consanguineous families can improve genetic analyses in SLI and suggest the involvement of additional genes in the causation of this disorder.